Sustainable development planning and green construction for building resilient cities: Russian experiences within the international context. (3rd April 2017) - Porfiriev, Boris N.; Dmitriev, Alexander; Vladimirova, Irina; Tsygankova, Anna
ABSTRACT: Within the international sustainable development goals agreed in 2015, strengthening of cities' resilience is especially important, providing for urban communities' effective preparedness, response to, recovery from as well as adaptation to hazardous impacts of multiple agents including those of environmental and climate change. Cities' resilience rests upon natural, social, political, human, economic and built capitals, with the built capital being a critical pillar. Consuming a significant share of the final energy, buildings and structures contribute to greenhouse gases emissions, exacerbating negative climate change implications for sustainable development. At the same time, the quality of construction and city planning preconditions provided by the built capital to urban communities to protect themselves from hazardous agents' impact. Given the above, this paper focuses on: (1) cities' resilience as a major factor of sustainable development and (2) the existing state and development perspectives of the sustainable development planning and green construction standards and certification systems including established international systems and the respective emerging system in Russia. It is argued that green construction policy and practice in general and green certification systems and green construction standards in particular serve as key catalysts in urban areas' transformation into resilient cities.